A new method for predicting the maximum wave height of ship-generated onshore slopes in restricted channel - Huang, Wei; Li, Shouqian; Lu, Yongjun; Zhang, Rui; Wang, Huai (Frontiers in Marine Science, 2023)
A new method for predicting the maximum wave height of ship-generated on-shore slopes in restricted channel Abstract：The ship-generated wave causes erosive damage to the slopes of inland waterways and confined waters such as the coastal zone. This critical issue is essentially associated with the navigational safety and sustainable development of coastlines, so it is vital to predicting the maximum wave height of the ship-generated wave (Hm) in the coastline of confined waters. The prediction equations of prior research works are mostly based on measured data and multiple regression analysis; however, this paper aims to propose a novel methodology to predict the maximum wave height of shipgenerated waves in confined waters. The maximum wave height caused by a selfpropelled ship under various conditions with confined water is measured by employing a water flume. Further, the relationships of functions in the prediction model equation are appropriately derived by dimensional analysis, and the prediction equation model is then solved via the particle swarm optimization algorithm (PSOA). The experimental results reveal that the maximum wave height of the ship-generated wave is seriously affected by the water depth of the channel (hc), the navigation speed of the ship (Vc), and the distance from the forecast point to the navigation line of the ship (Sc). In addition, the maximum wave height grows and then lessens, which touches its peak point in the region close to Frh=1. The dimensionless analysis indicates that the large wave height of the ship-generated wave can be expressed as a function of the channel depth (hc), ship speed (Vc), and the distance from the measurement point to the ship's navigation line (Sc) as: 22 relationship between the water depth of the channel and the coefficients is suitably outlined to obtain the maximum wave height prediction model equations for shipgenerated waves.